مرويات أبان بن تغلب في كتاب تهذيب الاحكام للطوسي(احكام الصيد انموذجاً ) (Journal of the College of Basic Education, 2024)
Narrations of Aban ibn Taghlib in the book Tahdheeb al-Ahkam by al-Tusi (Ahkam al-Sayd as an example(Narrations that showed the rulings on hunting and slaughtering in the field of refinement. The noble hadiths indicated the rulings on hunting and slaughtering in general, and consideration of hunting requires clarification of three matters: The first is regarding what its hunt is eaten, even if it is killed. Of the animals, it is limited to the marked dog, without other raptors of wild beasts and birds. If it is hunted with something else, such as a leopard or a tiger, or Other than the wildebeest, it is not permissible to do anything except what can catch its slaughter. The same applies if it is hunted with a falcon, an osprey, a sparrow hawk, and other birds’ prey Whether he is a teacher or not, as for the slaughtering of a sheep, one of the things considered in the slaughtering process is the movement of the animal after the completion of the slaughter, in order to indicate that it fell on the living, and the movement after slaughtering is sufficient in the slaughtering process to indicate the sweetness of the slaughter. Also, the ruling on slaughtering the animal at night is disliked. Slaughtering at night except in cases of necessity and other circumstances is disliked, and some of them are forbidden in slaughtering, and the point of slaughtering is to show servitude to God Almighty by slaughtering it in His name, and to show thanks for His blessings with it. My research consisted of three topics:The first topic: hunting baziThe second topic: slaughtering a sheThe third topic: The ruling on slaughtering zakat at night